The efficacy of “catch-up programmes” in South African high schools: a legal jinx - Nyoni, Jabulani (Faculty of Education, University of the Free State, 2013)
The South African State is mandated by Sections 28(2) and 29(1) of the South African Constitution to make provision for the education of a South African child in fulfilment of the child’s constitutional rights. Teacher Unions (TUs) and provincial Departments of Basic Education (DBEs) have often promised South African high school student body, in particular, and society at large, in general, that the compensation of time lost during a teachers’ strike is duly accounted for during the implementation of subsequent compensatory intervention strategy (CIS) “catch-up programmes”. The article argues that, as long as CIS “catch-up programmes” remain voluntary for both educators and learners, without the backing of enforceable mandatory legislative instruments that would hold public schools and DBEs to account, learners will continue losing valuable contact time, thereby jeopardising their chances of doing well in their academic school work and being denied their constitutional right to basic education in the process. The use of postpositivist, legal, rational, qualitative interpretive phenomenological analysis (IPA) was meant to explore how high school principals, teachers and students experienced CIS “catch-up programmes” implementation processes by DBEs (Smith & Osborn, 2008).
Keywords: Catch-up programme; Rule of law; Child’s best interests; Basic education